Bmi1 loss produces an increase in astroglial cells and a decrease in neural stem cell population and proliferation - Zencak, Dusan; Lingbeek, Merel; Kostic, Corinne; Tekaya, Meriem; Tanger, Ellen; Hornfeld, Dana; Jaquet, Muriel; Munier, Francis L; Schorderet, Daniel F; van Lohuizen, Maarten; Arsenijevic, Yvan (The Journal of neuroscience, 2005)
The polycomb transcriptional repressor Bmi1 promotes cell cycle progression, controls cell senescence, and is implicated in brain development. Loss of Bmi1 leads to a decreased brain size and causes progressive ataxia and epilepsy. Recently, Bmi1 was shown to control neural stem cell (NSC) renewal. However, the effect of Bmi1 loss on neural cell fate in vivo and the question whether the action of Bmi1 was intrinsic to the NSCs remained to be investigated. Here, we show that Bmi1 is expressed in the germinal zone in vivo and in NSCs as well as in progenitors proliferating in vitro, but not in differentiated cells. Loss of Bmi1 led to a decrease in proliferation in zones known to contain progenitors: the newborn cortex and the newborn and adult subventricular zone. This decrease was accentuated in vitro, where we observed a drastic reduction in NSC proliferation and renewal because of NSC-intrinsic effects of Bmi1 as shown by the means of RNA interference. Bmi1(-/-) mice also presented more astrocytes at birth, and a generalized gliosis at postnatal day 30. At both stages, colocalization of bromodeoxyuridine and GFAP demonstrated that Bmi1 loss did not prevent astrocyte precursor proliferation. Supporting these observations, Bmi1(-/-) neurospheres generate preferentially astrocytes probably attributable to a different responsiveness to environmental factors. Bmi1 is therefore necessary for NSC renewal in a cell-intrinsic mode, whereas the altered cell pattern of the Bmi1(-/-) brain shows that in vivo astrocyte precursors can proliferate in the absence of Bmi1.